Clinical characteristics and in-hospital outcomes in patients aged 80 years or over with cardiac troponin-positive acute myocardial infarction -J-MINUET study-. Issue 2 (February 2021) - Soeda, Tsunenari; Okura, Hiroyuki; Saito, Yoshihiko; Nakao, Koichi; Ozaki, Yukio; Kimura, Kazuo; Ako, Junya; Noguchi, Teruo; Suwa, Satoru; Fujimoto, Kazuteru; Nakama, Yasuharu; Morita, Takashi; et al.
Graphical abstract: AMI, acute myocardial infarction; NSTEMI, non-ST-segment elevation myocardial infarction; CAD, coronary artery disease; STEMI, ST-segment elevation myocardial infarction. Highlights: Patients with acute myocardial infarction (AMI) aged 80 years or over differ from those in younger population. Female gender, hypertension, chronic kidney disease, and prior cardiovascular disease were more frequent. Non-ST segment elevation AMI and multi-vessel coronary artery disease were more. This difference causes delayed or incomplete or both coronary revascularization. The difference results in poor in-hospital mortality and cardiac failure. Abstract: Background: The prevalence of acute myocardial infarction (AMI) in elderly people is increasing worldwide. However, their characteristics and prognosis have been rarely investigated. This study aimed to investigate the characteristics and prognosis in elderly patients with cardiac troponin-positive AMI. Methods: Consecutive patients with AMI from the J-MINUET study were divided into the following 3 groups: patients aged less than 65 years, those aged between 65 and 79 years, and those aged 80 years or over. Their characteristics and in-hospital outcomes were compared. Results: Patients with AMI aged 80 years or over had the highest incidence of female gender, and the highest incidence of hypertension, chronic kidney disease, and cardiovascular disease, such as peripheral artery disease, atrial fibrillation, and stroke, whereas they had the lowest body mass index, and the lowest incidence of current smoker, diabetes mellitus, and dyslipidemia. Patients with AMI aged 80 years or over had significantly longer onset to door time and longer door to device time, and lower peak creatine kinase (CK). The incidence of ST-segment elevation myocardial infarction (STEMI) was the lowest in the AMI patients aged 80 years or over, but the patients had a higher incidence of in-hospital death and cardiac failure than the other two groups. In addition, the presentation with STEMI and non-ST-segment elevation myocardial infarction with CK elevation among patients aged 80 years or over showed the highest incidence of in-hospital death and cardiac failure. Conclusions: J-MINUET showed different clinical characteristics between the aged and younger populations. The incidence of in-hospital death and cardiac failure in patients aged 80 years or over with AMI was poorer than their younger counterparts.